Prisons and Imprisonment An Introduction - Behan, Cormac; Stark, Abigail (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book examines prisons and imprisonment. Historically, prisons and prisoners have been a source of interest to the general public. However, despite near universal acceptance of imprisonment as a feature of society, the reality of prison life, and the effects it has on individuals and communities, remain a mystery to many. Using academic scholarship, empirical research, government papers, policy reports, and accounts from lived experiences of the institution, this book analyses the complexities and contradictions of prison life, the place of the prison in twenty-first century society, and its prospects for the future. It introduces readers to key debates surrounding the use of imprisonment, and encourages readers to interrogate conventional perspectives on an institution that reflects the society in which it is situated. Cormac Behan is Lecturer in Criminology at the Technology University Dublin, Ireland. Abigail Stark is Lecturer in Criminology at the University of Central Lancashire, UK. .
List of Tables and Figures -- List of Abbreviations -- Ch. 1: Introduction -- PART 1: PUNISHMENT AND PRISON -- Ch. 2: The Prison Emerges -- Ch. 3: Justifying Imprisonment as Punishment -- Ch. 4: Who is Punished? -- PART II: UNDERSTANDING THE EXPERIENCES OF THE PRISON -- Ch. 5: Life, Culture and Adaption in Prison -- Ch. 6: The Gendered Nature of Imprisonment -- Ch. 7: Prisoners and Protest -- Ch. 8: Prison in Popular Culture -- PART 111: THE PENAL FRAMEWORK -- Ch. 9: Prisoners' Rights -- Ch. 10: Governing Prisons -- Ch. 11: Working in Prison -- Ch. 12: The Architecture of Incarceration -- PART IV: POLITICS AND PENALITY -- Ch. 13: Comparative Penology -- Ch. 14: The Future of the Prison -- PART V: RESEARCHING PRISONS AND IMPRISONMENT -- Ch. 15: Researching Prisons and Imprisonment -- Glossary -- Index.
Keywords: Corrections; Punishment; Prison and Punishment